Does Early Decompressive Craniectomy Improve Outcome? Experience from an Active UK Recruiter Centre - E. García Vicente; V. Garnelo Rey; M. Manikon; S. Ashworth; M. H. Wilson (Case Reports in Critical Care)
Introduction. The results of the recent DECRA study suggest that although craniectomy decreases ICP and ICU length of stay, it is also associated with worst outcomes. Our experience, illustrated by these two striking cases, supports that early decompressive craniectomy may significantly improve the outcome in selected patients. Case Reports. The first patient, a 20-year-old man who suffered severe brain contusion and subarachnoid haemorrhage after a fall downstairs, with refractory ICP of 35 mmHg, despite maximal medical therapy, eventually underwent decompressive craniectomy. After 18 days in intensive care, he was discharged for rehabilitation. The second patient, a 23-year-old man was found at the scene of a road accident with a GCS of 3 and fixed, dilated pupils who underwent extensive unilateral decompressive craniectomy for refractory intracranial hypertension. After three weeks of cooling, paralysis, and neuroprotection, he eventually left ICU for rehabilitation. Outcomes. Four months after leaving ICU, the first patient abseiled 40 m down the main building of St. Mary’s Hospital to raise money for the Trauma Unit. He has returned to part-time work. The second patient, was decannulated less than a month later and made a full cognitive recovery. A year later, with a titanium skull prosthesis, he is back to part-time work and to playing football. Conclusions. Despite the conclusions of the DECRA study, our experience of the use of early decompressive craniectomy has been associated with outstanding outcomes. We are currently actively recruiting patients into the RESCUEicp trial and have high hopes that it will clarify the role of the decompressive craniectomy in traumatic brain injury and whether it effectively improves outcomes.